The political work of mayors: A look from Colombian law [El quehacer político del alcalde: Una mirada desde la normativa colombiana] (2016)
This article is intended to remark the importance of the mayor's position, from both its political dimension and also from his/her functions as a public server. For that purpose a revision to the corresponding law is made, from the Colombian Constitution to the legal decisions referred to the mayor's responsibility as a public server and as the representative of his/her town. Besides, an especial emphasis on the necessity of making sure the mayors know and apply the rules for public administration and territorial governance to duly accomplish their functions is made.